FACTORS THAT INFLUENCE FINANCIAL DISTRESS IN BANKING COMPANIES - Setiadi, Regina Angel; Setijaningsih, Herlin Tundjung; Verawati , Verawati (Graduate Program of Universitas Tarumanagara, 2024)
The purpose of this research is to obtain empirical evidence about the effects of managerial ownership, independent commissioner, leverage, and liquidity on Financial Distress in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. This research used 31 samples and 93 data from banking companies selected by the purposive sampling method. Data processing techniques uses secondary data which is processed using panel data regression analysis and processed using Microsoft Excel 2019 and Eviews version 12. The result of this research indicate that managerial ownership has a positive and significant effect on financial distress while independent commissioner, leverage, and liquidity have no significant effect on financial distress.